(In)Appropriate Online Behavior A pragmatic analysis of message board relations - Arendholz, Jenny (John Benjamins Publishing Company, 2013)
This descriptive and comprehensive study on the discursive struggle over interpersonal relations in online message boards is located at the fascinating interface of pragmatics and computer-mediated discourse - a research area which has so far not attracted much scientific interest. It sets out to shed light on the question how interpersonal relations are established, managed and negotiated in online message boards by giving a valid overview of the entire panoply of interpersonal relations (and their interrelations), including both positively and negatively marked behavior. With the first part of the book providing an in-depth discussion and refinement of the pivotal theoretical positions of both fields of research, students as well as professionals are (re-)acquainted with the subject at hand. Thus supplying a framework for the ensuing case study, the empirical part displays the results of the analysis of 50 threads (ca. 300,000 words) of a popular British message board.